(untitled) (Revista de Medicina Clinica, 2025)
Introduction: The objective of this systematic review is to analyze the available scientific evidence on the effects of omega-3 fatty acids on mental and neurological health. The objective of this systematic review is to analyze the available scientific evidence on the effects of omega-3 fatty acids on mental and neurological health. Methods: This systematic review is based on a rigorous search, analysis and synthesis of scientific literature that examines how omega-3 intake -especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)- affects clinical and functional outcomes in various mental and neurodegenerative disorders. Results: The review was carried out following the methodological guidelines proposed by the PRISMA statement, which ensured a transparent, exhaustive and carefully structured process at each stage. At the beginning, a total of 2,745 records were identified from four scientific databases recognized for their specialization in health and nutrition: PubMed, Web of Science, ScienceDirect and Google Scholar. Conclusion: The studies analyzed reveal that the therapeutic effects of omega-3 fatty acids on mental and cognitive health are highly contextual and heterogeneous, depending on factors such as age, clinical diagnosis, baseline state of the nervous system, type of intervention (dietary vs. supplementation) and the presence of inflammatory or antioxidant biomarkers.